Association between flavonoids, flavonoid subclasses intake and breast cancer risk: a case-control study in China. Issue 6 (November 2020) - Feng, Xiao-Li; Ho, Suzanne C.; Mo, Xiong-Fei; Lin, Fang-Yu; Zhang, Nai-Qi; Luo, Hong; Zhang, Xin; Zhang, Cai-Xia
Abstract : Anti-tumor effect of dietary flavonoids has been sustained by laboratory experiments, but epidemiological studies with breast cancer risk remained inconsistent and insufficient. This study aimed to investigate the associations between total and subclasses of flavonoid and breast cancer risk among Chinese population. This case-control study recruited 1522 eligible breast cancer cases and 1547 frequency-matched control subjects from June 2007 to July 2018 in Guangdong, China. Dietary intake was obtained by face-to-face interview using a validated food frequency questionnaire. Odds ratios and 95% confidence intervals were calculated by multivariable logistic regression models. After adjusting for potential confounders, inverse associations were observed between total flavonoids, anthocyanidins, proanthocyanidins, flavanones, flavones, flavonols and isoflavones and overall breast cancer risk. Comparing the highest versus the lowest quartile, odds ratio (95% confidence interval) was 0.66 (0.54–0.82) for total flavonoids, 0.61 (0.49–0.75) for anthocyanidins, 0.67 (0.54–0.83) for proanthocyanidins, 0.71 (0.57–0.88) for flavanones, 0.48 (0.39–0.60) for flavones, 0.51 (0.41–0.63) for flavonols and 0.67 (0.54–0.83) for isoflavones, respectively. No significant association was found between flavanols, flavan-3-ol monomers, theaflavins and breast cancer risk. Stratified analysis by menopausal status and estrogen receptor/progesterone receptor status showed that the associations of total flavonoids, most flavonoid subclasses with breast cancer risk were generally not modified by menopausal or estrogen receptor/progesterone receptor status. This study indicates that total flavonoids and most flavonoid subclasses intakes were inversely associated with breast cancer risk. Abstract : Supplemental Digital Content is available in the text.